Address System in Korea - Kwak, Byungyong; Dangol, Susheel (Journal on Geoinformatics, Nepal, 2019)
Address is basic information to find location as a code and an abstract concept for representing a location on the Earth’s surface. It is also used in many areas such as public administration, legal and official areas, land titling etc. In Korea, address is recognized as the base information of life for the people as well as the key information of activities for organizations and companies in nationwide. Korea’s address system used land parcel numbers which was given to each piece of land for identification since 1918, which was before the introduction of the road name address system. The aim of the study is to find out how Korean address system has changed and how to manage, maintain, and use the address information in Korea.